The Influence of Organizational Culture and Work Discipline on Employee Performance of PT. BFI Finance Indonesia Tbk. - Thifal Rizani, Ainun; Shinta Oktafien, (Technium Social Sciences Journal, 2020)
Performance problems are of course inseparable from the process of results and efficiency, in this case performance or work performance is the quality and quantity of work achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Many factors influence employee performance, both from within and from within the organization where the employee works. Of the many aspects that are considered important in employee performance, they can be classified into two factors, namely organizational culture and discipline. The purpose of this study was to determine and analyze Work Discipline on Employee Performance at PT. BFI Finance Indonesia Tbk. simultaneously or partially. This study usesmethods descriptive and verificationwhere the population is drawn from the employees of PT.BFI Finance Indonesia Tbk, by using a saturated sampling technique in sampling, this is done because the population is relatively small. Multiple Linear Regression Analysis, coefficient of determination, and hypothesis testing. Based on the calculation of the coefficient of determination and hypothesis testing, it shows that organizational culture has a significant effect on employee performance variables, work discipline has a significant effect on employee performance variables and simultaneously there is a significant effect of organizational culture and work discipline on employee performance.